DESAIN PRODUK JASA MODEL INVESTASI DENGAN DUAL PROFIT - Lie Liana (Jurnal Ilmiah Dinamika Teknik, 2012)
It required some creativity and innovation to design an investment model that can generate substantial funds with an elegant way and making the investor get dual profit. Two advantages that an investor can help each other, which means he invests for heavenly treasures, and the investment is likely to evolve as well, which means investors are also investing for worldly possessions. The design investment model is able to capture the number of investor, both from the top, middle or bottom, meaning all levels of society can become investors in accordance with their respective capabilities. The design model of this investment is to be managed by people whose integrity has been tested so that investors will never be harmed. Business investment model is also not to be afraid, because the system here does not allow investor harm. Besides this investment model design can involve a lot of labor depends on the size of the investment with the system is not time-bound work Key words : desain, investment model, dual profit, investor